Rancang Bangun Alat Pemberi Pakan Hewan Peliharaan Otomatis Berbasis IoT (Internet of Things) - Ramadhan, Farhan; Fithry Tahel (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
An automatic animal feeder is a tool used by cat owners to help ease their daily activities. When it comes to caring for animals at home, the most important thing is regular feeding. Regular feeding can make pets healthier and maintain their appetite. This is done with the aim of increasing pet owners' awareness of the food they feed their pets. Therefore, this automatic feeder was designed based on the Internet of Things (IoT). It consists of several components that are designed and connected to electricity and the internet. NodeMCU ESP8266 and Arduino IDE are the main components in the design of this device, allowing it to be operated using a smartphone. On the smartphone, users must download Blynk as a remote control for the automatic feeder. Through the Blynk app, users can automatically schedule feeding times for their pets. This research aims to assist pet owners who often leave their pets at home, ensuring their feeding times are maintained.